Antecedents, moderators, and outcome of empowerment of the line managers in human resource activities / Yusliza Mohd. Yusoff - Mohd. Yusoff, Yusliza (2009)
Within Strategic Human Resource Management (HRM), empowerment is sponsored as a means to seek greater purpose and value for HRM in the organization. Even though the role of line in HRM is widely acknowledged, the devolution of greater powers by HR is enjoined as the way forward. It is claimed that the empowerment of line in HR matters, makes HR more business-minded and the line more people oriented. It is claimed that empowerment is necessitated by market conditions. This study investigated this development systematically through the identification of antecedents (intensity of market competition, organizational structure, role of the HR department, and inter-functional cooperation) and outcome (HRM effectiveness) of empowerment of the line managers in HR activities. This study also crucially examined the willingness of HR manager and readiness of line manager as moderators of the relationship between the antecedents and empowerment of the line. The data were obtained from 108 large manufacturing and service firms through mail questionnaire survey. The informants of this study consisted of HR and line managers. Returned questionnaires were only included organizations which were represented by HR manager and at least one line manager. Data collected were analyzed using principal components factor analysis, descriptive statistics, Cronbach's alpha, and Pearson correlations. Hypotheses were tested using hierarchical multiple regression analysis. Type of organization (manufacturing and service) is controlled for the purpose of testing the hypotheses because it may influence the dependent variable. The findings indicated that business partner role, employee champion role, and inter-functional cooperation had positive relationship with empowerment of the line. Additionally, it was found that centralization is negatively related to empowerment of the line. Contrary to expectations, intensity of market competition, formalization, and administrative expert role were not significantly related to empowerment of the line. In testing the effect of outcome variable, results of this study showed that empowerment of the line had positive relationship with both the effectiveness of the HR roles and the effectiveness of the HR contributions. Further, the results indicated that the willingness of HR manager and readiness of line manager did not significantly moderate the relationship between the antecedents and empowerment of the line. The study by testing important claims in the discipline helps to clarify important conceptual and theoretical points. The practical implications of the study as well as suggestions for future studies are also presented.